Picture-Induced Semantic Interference Reflects Lexical Competition during Object Naming - Aristei, Sabrina; Zwitserlood, Pienie; Abdel Rahman, Rasha (Frontiers in Psychology, 2012)
With a picture-picture experiment we contrasted competitive and non-competitive models of lexical selection during language production. Participants produced novel noun-noun compounds in response to two separately displayed categorically related or unrelated objects (e.g. depicted objects: apple and cherry; naming response: "apple-cherry"). We observed a classic interference effect, with slower naming for related relative to unrelated pairs. This finding suggests that previous failures to find strong interference induced by context pictures may be due to the weakness of picture-induced lexical competition. Apparently, the production of both picture names within one integrated compound word enhances lexical activation and thus, increases lexical competition, resulting in measurable interference effects. We conclude that lexical selection is competitive, given that interference due to pictures is not due to privileged access of word stimuli to the articulatory buffer.